A meta-analysis of host specificity in Neotropical hard ticks (Acari: Ixodidae) - Nava, Santiago (2013)
Host specificity of Neotropical hard ticks (Acari: Ixodidae) was analyzed by using the number of hosts species for each tick species and the index of host specificity STD*, which integrates phylogenetic and ecological information. The analyses were based on 4172 records of hard ticks collected from wild and domestic tetrapods. Most tick species included in this study were associated with three to 20 host species. No tick species has been associated either with a single species or with a single genus of host. It was found that the number of host species is sensitive to sampling effort, but not the STD*. The most frequent values of STD* were between 2.5 and 3.5, which shows that the host species more frequently used by Neotropical hard tick species belong to different families or different orders. Immature stages tend to use a broader taxonomic range of hosts than adults, and the interpretation of both measures of host specificity used in this study led to the conclusion that the impact of non-endemic hosts does not alter the patterns of host specificity in Neotropical hard ticks. The index STD* showed that a high proportion of tick species has phylogenetically unrelated species as principal hosts. The conclusion reached in this work indicates that strict host specificity is not common among Neotropical hard ticks and suggests that the influence of tick ecology and evolution of habitat specificity, tick generation time, phenology, time spent off the host and the type of life-cycle could be more important than hosts species.